2007
DOI: 10.1183/09031936.00001007
|View full text |Cite
|
Sign up to set email alerts
|

Initiating oral breathing in response to nasal loading: asthmaticsversushealthy subjects

Abstract: Factors influencing nasal versus oral breathing in asthmatics are not well understood. The current authors hypothesised that asthmatic subjects have enhanced perception of nasal threshold loads, and switch from nasal to oral breathing at a lower load than healthy subjects.In total, 15 mild asthmatic and 20 healthy control subjects breathed nasally via an inspiratory threshold loading device. Nasal loading was progressively increased until subjects switched to oral breathing. Load perception at switching was ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…(24) Some studies have assessed cardiorespiratory function in subjects under conditions that induce mouth breathing. (25)(26)(27)(28) Ribeiro & Soares (25) observed that some spirometric indices (FEF 25-75% and maximal voluntary ventilation) were below and decreased cervical lordosis in 30 mouthbreathing children. The results of those studies corroborate those of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(24) Some studies have assessed cardiorespiratory function in subjects under conditions that induce mouth breathing. (25)(26)(27)(28) Ribeiro & Soares (25) observed that some spirometric indices (FEF 25-75% and maximal voluntary ventilation) were below and decreased cervical lordosis in 30 mouthbreathing children. The results of those studies corroborate those of our study.…”
Section: Discussionmentioning
confidence: 99%
“…(26) In subjects with asthma, less nasal resistance is required in order to induce mouth breathing, and, when mouth breathing occurs, there is a decrease in pulmonary function and a greater predisposition to bronchial obstruction. (27) Melissant et al (28) induced upper airway obstruction during exercise and found that there were decreases in minute ventilation and CO 2 production. The responses of the subjects included hypoventilation, hypoxia, and hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
“…A few authors have evaluated cardiorespiratory function in mouth breathing subjects [27][28][29][30] . Ribeiro & Soares 27 found lower than predicted spirometry test values (forced expiratory flow 25%-75%, and maximum voluntary ventilation), characterizing a mostly mild to moderate obstructive type ventilation disorder in mouth breathers.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal and oral respiratory pathways of thermostasis The majority of healthy adults are nasal breathers at resting tidal breathing or light exertion (Niinimaa et al, 1980;Hallani et al, 2008), but changes in the partitioning of the breathing cycle among nasal, oronasal, and oral components can impact the respiratory portion of heat exchange, as well as microclimate (i.e. respirator dead space) heat and moisture content.…”
Section: Pfm Impact On Human Thermoregulation 103mentioning
confidence: 99%